Propofol Sedation in Diagnostic Upper Gastrointestinal Endoscopy - Christophorus Simadibrata; Benvenuto Axel; Syahrizal Syahrizal; Dina Ikawari; Paulus Simadibrata; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2020)
Background: Sedation are commonly used these days in patients that having gastrointestinal endoscopy. Propofol is sedative agent that commonly used in endoscopy procedure.Method: All patients who were performed diagnostic EGD in Abdi Waluyo Hospital’s Gastrointestinal Endoscopy Unit from January 1st 2017 – 31st December 2017, included in this study. The amount of Propofol, duration during hypnosis/sedation and adverse effects were all recorded.Results: 170 patients were performed diagnostic EGD with Propofol sedation, most of them were male (87 patients, 51,5%). The median age was 48,78 + 14. The median Body Mass Index (BMI) was 24.45. The median of duration of hynosis (sedation) during EGD was 5 minutes. The median of propofol total dose during EGD was 180 mg. Adverse effects that found during Propofol sedation are muscle twitching(10.6% patients) and pain in area of injection(80% patients). Conclusion: The duration of propofol hypnosis/sedation during Esophagogastroduodenoscopy examination was 5 minutes. Propofol total dose needed for diagnostic EGD was 180 mg. The common adverse effects of propofol are muscle twitching and pain in area of injection.